The safe administration of medication: Nursing behaviours beyond the five-rights. (May 2019) - Martyn, Julie-Anne; Paliadelis, Penny; Perry, Chad
Abstract: This paper discusses the findings from the observation phase of a more extensive, appreciative inquiry qualitative study exploring registered nurses' experiences of administering medications. The observations aimed to explore the participants' application of the five-rights of medication administration in practice. Twenty registered nurses working in inpatient medical/surgical units at a regional Australian hospital were observed administering medications from the commencement to the completion of their shift. A data collection tool based on the five-rights of medication administration was used. The findings indicated that medication administration was not as routine as the rights framework suggests. Indeed, what was observed rarely reflected all the criteria of the rights framework. Notably, in practice, some of the rights were unable to be observed because the critical thinking that underpins the rights are implicit. However, the participants were observed to implement strategies beyond those described by the rights framework that ensured safe and timely medication administration. In brief, medication administration in contemporary healthcare settings is more complicated than the linear process suggested by the rights framework. So more attention is warranted, to the safe practice strategies of nurses who, to deal with complex clinical contexts. Their person-centred strategies respond to patient circumstances and maintain safety.